Assessing five decades of garden bee studies - Bell, Nicole C. S.; Ascher, John S.; Hayes, Jen J.-M.; Mead, Mallory; Langellotto, Gail A. (Frontiers in Sustainable Cities, 2023)
Urban garden spaces are potentially important habitats for bee conservation. Gardens can host diverse flora, which provide floral resources across foraging seasons for bee species. Recent reviews have focused on the impacts of cityscapes on urban bee assemblages in different green spaces. Urban gardens are distinct from other urban green spaces, and bee communities in urban spaces have been an increasing topic of study over the past few decades. We reviewed 28 urban garden bee studies spanning five decades and 14 countries to compile an original metadataset of bee species' functional traits to understand the conservation value of gardens, identify gaps in bee sampling efforts, and summarize the calls to action included by their authors. Studies of urban garden bees have documented between 674 (conservative count, excluding morphospecies) to 830 (liberal count, including morphospecies) bee species. Urban garden bee communities were taxonomically and functionally diverse, although bee species that were non-eusocial, ground-nesting, generalist foragers, and native were most common in garden habitats. The proportion of parasitic bee species and specialist foragers found in urban gardens was comparable to proportions for global bee taxa. This suggests that gardens contain the hosts and forage needed to support bees with specialized life history requirements, and thus represent high quality habitat for a subset of bee communities. Garden bee research was strongly biased towards the northern hemisphere, which signifies a large gap in our understanding of garden bee communities in other regions The variety of, and nonstandard sampling methods in garden bee research makes it difficult to directly compare results between studies. In addition, both intentional low taxonomic resolution and a lack of collaboration with taxonomists constrains our understanding of bee diversity. Our analyses highlight both successes of past urban garden bee studies, and areas of opportunity for future research as we move into a sixth decade of garden bee research.